2018
DOI: 10.31758/omegajphysphyseduc.v4i1.1
|View full text |Cite
|
Sign up to set email alerts
|

Simulating the Aerodynamics Profiles of NACA 4312 Airfoil in Various Incoming Airspeed and Gurney Flap Angle

Abstract: Simulations of the aerodynamics performance of NACA 4312 airfoil at various gurney flap angles and incoming airspeed (wind velocities) have been conducted. The gurney flap's size was set at 5.0% length of the chord line.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
0
0
Order By: Relevance
“…The research results indicated that, with an increase in height, both lift and drag increased, and a Gurney flap height of 1.5% chord length performed the best within the studied range. Sumaryada et al [11] examined the effects of different Gurney flap installation angles on the aerodynamic performance of the NACA4312 foil. After simulating the aerodynamic performance of the foil at different wind speeds, they found that, within the range of the installation angle studied, increasing the installation angle led to an increase in lift and a decrease in drag of the foil.…”
Section: Introductionmentioning
confidence: 99%
“…The research results indicated that, with an increase in height, both lift and drag increased, and a Gurney flap height of 1.5% chord length performed the best within the studied range. Sumaryada et al [11] examined the effects of different Gurney flap installation angles on the aerodynamic performance of the NACA4312 foil. After simulating the aerodynamic performance of the foil at different wind speeds, they found that, within the range of the installation angle studied, increasing the installation angle led to an increase in lift and a decrease in drag of the foil.…”
Section: Introductionmentioning
confidence: 99%